Extensive spinal epidural abscess caused by Staphylococcus epidermidis: A case report and literature review - Pi, Yang-wei; Gong, Yan; Jiang, Jia-jia; Zhu, De-jin; Tong, Yue-xin; Jiang, Li-ming; Zhao, Dong-xu (Frontiers in Surgery, 2023)
Background: Extensive spinal epidural abscess (SEA) is an exceptional and threatening condition that requires prompt recognition and proper management to avoid potentially disastrous complications. We aimed to find key elements of early diagnosis and rational treatments for extensive SEA. Case presentation: A 70-year-old man complained of intense pain in the cervical-thoracic-lumbar spine that radiated to the lower extremity. Laboratory test results revealed a marked increase in all indicators of infection. The spinal magnetic resonance imaging (MRI) revealed a ventral SEA extending from C2 to L4. Owing to the patient’s critical condition, laminectomy, drainage, and systemic antibiotic therapy were administered. And the multidrug-resistant Staphylococcus epidermidis was detected in the purulent material from this abscess. Results: Postoperative MRI revealed diminished epidural abscess, and the clinical symptoms were dramatically and gradually relieved after two rounds of surgery and systemic antibiotic therapy involving the combination of ceftriaxone, linezolid, and rifampicin. Conclusions: A comprehensive emergency assessment based on neck or back pain, neurological dysfunctions, signs of systemic infection, and MRI are important for early diagnosis of extensive SEA. Further, the combination of laminectomy, drainage, and systemic antibiotic therapy may be a rational treatment choice for patients with SEA, especially for extensive abscess or progressive neurological dysfunction.